Efikasi Diri dan Harapan Sebagai Prediktor Burnout pada Karyawan - Hidayat, Novi; Estu , Bekti; Ayu Widyautami, Putri; Maulana, Iksal (Lembaga Pengembangan Kinerja Dosen, 2025)
Burnout is a critical psychological phenomenon among employees, characterized by emotional exhaustion, reduced motivation, and diminished professional efficacy. This study aims to examine the predictive role of self-efficacy and hope on employee burnout. Using a quantitative approach with an ex post facto design, data were collected from 150 employees in Central Java, Indonesia, selected through multistage random sampling followed by purposive sampling. Measurement instruments included the Burnout Inventory (0,911), General Self-Efficacy Scale (0,887), dan Hope Scale (0,90), all of which demonstrated high reliability. Data were analyzed using multiple regression with SPSS. The results revealed that both self-efficacy and hope significantly predicted burnout, explaining 69.3% of the variance. Employees with higher self-efficacy tended to adopt adaptive coping strategies and were less vulnerable to emotional exhaustion, while those with higher levels of hope maintained stronger motivation and engagement despite work pressures. These findings highlight the importance of fostering psychological resources such as self-efficacy and hope to protect employees from burnout. Organizations are recommended to design psychological interventions and workplace policies to enhance employee resilience. Future research should expand the scope by incorporating other psychosocial variables and diverse organizational contexts to strengthen generalizability.